Epidural Electronics: Epidural Electrotherapy for Epilepsy (Small 30/2018). Issue 30 (26th July 2018) - Park, Sung‐Won; Kim, Jejung; Kang, Minpyo; Lee, Wonho; Park, Byong Seo; Kim, Hansung; Choi, Se‐Young; Yang, Sungchil; Ahn, Jong‐Hyun; Yang, Sunggu
Abstract : In article number1801732, Sungchil Yang, Jong‐Hyun Ahn, Sunggu Yang, and co‐workers present an approach of diagnostic and therapeutic epidural electronics. Ultrathin graphene electrodes are integrated into an electrocorticography (ECoG) array, therein simultaneously sampling brain signals in a large area for diagnostic purposes, and delivery of electrical pulses for treatment of epilepsy.